1979
DOI: 10.1083/jcb.81.2.382
|View full text |Cite
|
Sign up to set email alerts
|

Direct visualization of the binding and internalization of a ferritin conjugate of epidermal growth factor in human carcinoma cells A-431.

Abstract: We have prepared a conjugate of epidermal growth factor (EGF) and ferritin that retains substantial binding affinity for cell receptors and is biologically active. Glutaraldehyde-activated EGF was covalently linked to ferritin to produce a conjugate that contained EGF and ferritin in a 1:1 molar ratio. The conjugate was separated from free ferritin by affinity chromatography using antibodies to EGF. Monolayers of human epithelioid carcinoma cells (A-431) were incubated with EGF:ferritin at 4~ and processed for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
272
6
1

Year Published

1982
1982
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 510 publications
(298 citation statements)
references
References 6 publications
19
272
6
1
Order By: Relevance
“…S1). This suggests that the EGFR meets the Ndfip proteins following its endocytosis, which rapidly follows EGF binding (20).…”
Section: Resultsmentioning
confidence: 99%
“…S1). This suggests that the EGFR meets the Ndfip proteins following its endocytosis, which rapidly follows EGF binding (20).…”
Section: Resultsmentioning
confidence: 99%
“…It is worth noting that the binding of EGF ligand to its cognate receptor at ambient temperature (25°C ≤ temp ≤ 37°C), initiates a signaling cascade that involves the internalization of the activated receptor into endocytic vesicles of the cell (49,50). Figure 4D shows the confocal microscopy image of a QD585-M2 bead (160,000 Qdots/bead) next to a Qdot-EGF ligand activated A431 cell (100,000 Qdots per cell) (51).…”
Section: Applicability Of Qdot Calibration Beads On Cells: Determinatmentioning
confidence: 99%
“…A role for endocytosis in the regulation of RTK signaling was first proposed in the late 1970s when it was observed that the EGFR was internalized following application of ligand (Haigler et al 1979). Since the mid-1980s, the role that endocytosis plays in regulating EGFR signaling has been the subject of intense investigation and controversy (Leof 2000;Ceresa et al 2001).…”
Section: Endocytosis Regulates Rtk Signalingmentioning
confidence: 99%